PENYATUAN ZONA WAKTU DAN PENGARUHNYA TERHADAP PENETAPAN AWAL WAKTU SHALAT - Rahmi, Nailur (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2014)
The problem of this research was that the society’s confusion about uniting of three time zones (WIB, WIT, and WITA) to become one time (WITA), especially moslem people in Indonesia. Due to this phenomena, it made them got confusion in determining the correct time of doing cumpolsory prayers. Realizing this problem the research was done to study about the uniting of those times that were lied on WITA.Actually, there were two formulas that could be used to solve that problem, namely: first, by using ordinary formula in which time zone of WIB was added one hour and by delaying one hour for time zone of WITA, and second, by calculating the time by using the prior time prayer and correcting the formula refers to several formulas in time zone of WITA. Therefore, by uniting of those three time zones did not give negative effects on determining time prayers.